Low-Frequency Intravesical Electrical Stimulation for the Treatment of Acute Urinary Retention: A Promising Therapeutic Approach - Cao, Tingting; Xie, Bing; Yang, Siyuan; Wang, Jiaqi; Yang, Xiao; Shen, Boqiang; Lin, Xueke; Sun, Xiuli; Wang, Jianliu (Frontiers in Medicine, 2021)
Acute urinary retention (AUR) is a troublesome urological disease, which causes various lower urinary tract symptoms. However, only few studies explored and evaluated the effective treatments to improve AUR. We aimed to find an effective approach to cure AUR through comparing the efficacy of existing classical low-frequency transcutaneous electrical nerve stimulation (TENS) and novel intravesical electrical stimulation (IVES). A total of 24 AUR female rats were divided into three groups as follows: control, TENS and IVES groups. Rats in the control group had no fake stimulation. Rats in the TENS and IVES groups underwent transcutaneous or intravesical stimulation of a symmetrical biphasic rectangular current pulse with a frequency of 35 Hz, 30 min per day, for seven consecutive days. IVES significantly reduced the actin expression in submucosal layer but increased its expression in detrusor layer (p=0.035, p=0.001). The neovascularization in submucosal layer in the IVES group was significantly increased compare to the other two groups (p=0.006). Low-frequency IVES performed better than TENS in terms of simultaneously relieving bladder hyperactivity, accelerating epithelial recovery and strengthening detrusor muscle. IVES may be a promising therapeutic approach for bladder dysfunction, specifically for AUR and overactive bladder in clinical practice.